Improving Students’ Oral Skill Using Photovoice - Sarno La Janu; Abdul Halim; Sarjaniah Zur (AL LUGHAWIYAAT, 2020)
The objective of this research is to improve Grade XI students’ oral skills of MAN 1 Kendari. This research is classroom action research. It is conduct in two cycles, which is held for three meetings in the first cycle and three meetings in the second cycle. The subjects of this research are 29 students of class XI English Major at MAN 1 Kendari. The instruments of the study are observation sheet and students’ reflection. The actions implement in this research are using photovoice in teaching and learning process of speaking, implementing picture-based activities, giving feedback to students’ performances, accustoming students to speak English, and some other activities (actions). The results of the research show that the use of photovoice in the teaching and learning process of speaking is believe to be effective to improve the students’ speaking skills. The students’ motivation also increases. The result revealed that the mean score of the students’ speaking performance increase from 57% in the first cycle to 81% in the second cycle.Key words: Classroom Action Research, Oral Skill and Photovoice